2005
DOI: 10.1111/j.1532-5415.2005.53406.x
|View full text |Cite
|
Sign up to set email alerts
|

The Life Cycle of Bruises in Older Adults

Abstract: Accidental bruises occur in a predictable location pattern in older adults. One cannot reliably predict the age of a bruise by its color.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 13 publications
4
50
0
Order By: Relevance
“…In addition, a further confounding factor is the marked inter-and intra-observer variability that occurs in describing the color of bruises [7,8]. It has been suggested that the only statement that can be reliably made about the color of bruises is that a yellow bruise is at least 18 h old [9], although even this has been challenged [5,7,[10][11][12]. While it is possible that spectrophotometry may provide a useful technique in the future for standardizing the evaluation of hemoglobin breakdown products in the skin, this is not routinely used [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a further confounding factor is the marked inter-and intra-observer variability that occurs in describing the color of bruises [7,8]. It has been suggested that the only statement that can be reliably made about the color of bruises is that a yellow bruise is at least 18 h old [9], although even this has been challenged [5,7,[10][11][12]. While it is possible that spectrophotometry may provide a useful technique in the future for standardizing the evaluation of hemoglobin breakdown products in the skin, this is not routinely used [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Research has confirmed a relation between elderly abuse and ill health in studies concerning, for instance, domestic violence 8,13 limited populations such as primary care settings 14 and independent living settings 15,16 . Physical abuse may have both physical and psychological consequences [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 93%
“…Over the course of several years, two grants were obtained in sequence from the National Institute of Justice to study noninflicted and inflicted bruises in older adults. The results of both of these studies were eventually published in the Journal of the American Geriatrics Society (Mosqueda, Burnight, & Liao, 2005;Wiglesworth et al, 2009).…”
Section: How the Center Workmentioning
confidence: 95%